battery
Patent Information
- Application Number
- CN202610954627.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-29
- Publication Date
- 2026-10-13
AI Technical Summary
目前商用锂离子电池的负极主要以石墨为主,其低比容量特性逐渐难以满足发展需求,硅材料是目前所发现的具有最高理论储锂容量的负极材料,其比容量远远高于目前商品化的石墨负极材料,可以显著提高锂离子电池的能量密度,但是在实际应用中发现,硅材料存在着首次库伦效率较低的缺点,严重限制了正极容量的发挥
(1)在本发明中,在负极活性层中嵌入锂单质能够弥补SEI膜的生成对活性锂的不可逆损耗,并在电池循环过程中实现活性锂的缓释,不仅提升电池的首次库伦效率,还能够提升电池的能量密度。
Smart Images

Figure CN122907704A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and more specifically to a battery. Background Technology
[0002] With the commercialization and promotion of lithium-ion batteries, their high energy density has led to successful applications in 3C consumer electronics and electric vehicles. Currently, the anode material for commercial lithium-ion batteries is mainly graphite, but its low specific capacity is gradually becoming insufficient to meet development needs. Silicon material is currently the anode material with the highest theoretical lithium storage capacity, and its specific capacity is far higher than that of commercially available graphite anode materials, which can significantly improve the energy density of lithium-ion batteries. However, in practical applications, it has been found that silicon material has a relatively low initial coulombic efficiency, which severely limits the realization of the positive electrode capacity. Although the commonly used lithium replenishment methods in existing technologies help improve the energy density of the battery, the high chemical reactivity of lithium metal often poses safety risks, especially affecting the safety performance of the battery at high temperatures. Therefore, how to balance the energy density, initial coulombic efficiency, and furnace temperature safety performance of lithium-ion batteries has become one of the key and difficult points in expanding the application of silicon-based anode batteries. Summary of the Invention
[0003] The purpose of this invention is to provide a battery in which the negative electrode includes a protective layer disposed on the surface of the negative electrode active layer, the protective layer comprising lithium carbonate and elemental lithium. When this negative electrode is used in a battery (especially a silicon-based negative electrode battery), it can achieve both high energy density, initial coulombic efficiency and furnace temperature safety performance.
[0004] In related technologies, silicon-carbon materials used as anodes can significantly improve battery energy density. However, they undergo significant volume changes during battery cycling, and the surface SEI film is prone to repeated rupture and formation, leading to continuous consumption of active lithium. Simultaneously, silicon-carbon materials have poor intrinsic conductivity, resulting in low initial coulombic efficiency. Lithium replenishment of the anode is a common method to improve initial coulombic efficiency, compensating for the irreversible loss of active lithium caused by SEI film formation during formation and cycling, thereby increasing energy density and initial coulombic efficiency. However, conventional lithium replenishment often involves applying a uniformly thick and consistent lithium replenishment material to the surface of the anode. When elemental lithium is used, the surface of the anode contains a large amount of highly reactive elemental lithium, which readily reacts violently with moisture and oxygen in the air, increasing safety hazards and potentially leading to battery combustion or explosion.
[0005] In order to overcome the problems existing in the prior art, the inventors of this invention discovered through experimental research that simultaneously introducing elemental lithium and a protective layer with low chemical reactivity into the negative electrode sheet can achieve both high energy density and good first coulombic efficiency of silicon-based negative electrode batteries, while avoiding the safety hazards caused by the high activity of elemental lithium. Specifically: Introducing elemental lithium into the silicon-doped anode can compensate for the active lithium consumed during the formation of the SEI film during the first charge, reducing irreversible loss of active lithium and allowing more lithium ions to be used for reversible energy storage, significantly improving the battery's energy density and initial coulombic efficiency. Simultaneously, the elemental lithium retained within the anode can achieve slow release of active lithium throughout the battery's lifespan, maintaining a stable inventory of active lithium and mitigating capacity decay during cycling. Secondly, a protective layer containing lithium carbonate is applied to the surface of the anode to protect the elemental lithium, preventing chemical reactions with air and moisture, facilitating the transfer and storage of the anode, reducing safety hazards in lithium-ion battery replenishment, and improving the replenishment effect. This further improves the initial coulombic efficiency and furnace temperature safety performance of high-energy-density batteries. Furthermore, the protective layer increases the surface roughness of the anode, improving the electrolyte contact angle, enhancing the electrolyte's wettability to the anode, and increasing lithium-ion transport efficiency.
[0006] Based on this, the present invention proposes the following technical solution: The present invention provides a battery comprising an electrode assembly, the electrode assembly comprising a positive electrode, a separator, and a negative electrode stacked thereon, the negative electrode comprising a negative current collector and a negative active layer located on at least one side surface of the negative current collector, the negative active layer comprising a negative active material, the negative active material comprising a silicon-carbon material; a protective layer comprising lithium carbonate is disposed on the side surface of the negative active layer opposite to the negative current collector, the protective layer being connected to the silicon-carbon material and at least a portion of the lithium carbonate; the protective layer comprising elemental lithium.
[0007] By employing the above technical solution, the present invention has at least the following advantages compared with the prior art: (1) In this invention, embedding elemental lithium in the negative electrode active layer can compensate for the irreversible loss of active lithium caused by the formation of SEI film and achieve the slow release of active lithium during battery cycling, which not only improves the first coulombic efficiency of the battery, but also improves the energy density of the battery.
[0008] (2) In this invention, a protective layer is provided on the surface of the negative electrode active layer. The protective layer has low chemical reactivity and can protect the highly active lithium element in the negative electrode from contact with air and moisture, reducing safety hazards and the probability of battery fire and explosion. At the same time, it increases the surface roughness of the negative electrode and promotes electrolyte wetting, thereby improving the furnace temperature safety performance, energy density and first coulombic efficiency of the battery.
[0009] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein. Attached Figure Description
[0010] Figure 1 The diagram shown is a schematic diagram of the negative electrode sheet along the thickness direction in one embodiment of the present invention.
[0011] Figure 2 The diagram shown is a schematic representation of the negative electrode sheet along the extension direction of the tab in one embodiment of the present invention.
[0012] Figure 3 The diagram shown is a schematic diagram of the negative electrode tab in one embodiment of the present invention.
[0013] Reference numerals: 1. Negative electrode; 2. Positive electrode; 4. Separator; 10. Negative electrode current collector; 11. Negative electrode active layer; 12. Elemental lithium; 13. Protective layer; 2. Negative electrode tab; 31. First region; 32. Second region; 33. Third region; 34. Fourth region; 35. Fifth region. Detailed Implementation
[0014] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.
[0015] The present invention provides a battery comprising an electrode assembly, the electrode assembly comprising a positive electrode, a separator and a negative electrode stacked thereon, the negative electrode comprising a negative current collector and a negative active layer located on at least one side surface of the negative current collector, the negative active layer comprising a negative active material, the negative active material comprising a silicon-carbon material.
[0016] In this invention, a protective layer is provided on the surface of the negative electrode active layer facing away from the negative electrode current collector. The protective layer includes lithium carbonate, and the silicon-carbon material is connected to at least a portion of the lithium carbonate. Here, "the silicon-carbon material is connected to at least a portion of the lithium carbonate" can be understood as meaning that there are contact sites between the silicon-carbon material and at least a portion of the lithium carbonate, and the proportion of lithium carbonate in contact with the silicon-carbon material can be less than 100% or equal to 100% of the total lithium carbonate.
[0017] In this invention, the protective layer also includes elemental lithium.
[0018] In this invention, whether the protective layer contains elemental lithium can be determined by conventional testing methods in the art, such as laser induced breakdown spectroscopy (LIBS) using a laser spectrometer. The laser type is Nd:YAG (neodymium-doped yttrium aluminum garnet laser), the spot size is 10 μm, and the laser wavelength is 355 nm. Specifically, the battery is discharged to 0% SOC, the negative electrode is disassembled and removed, soaked in dimethyl carbonate (DMC) solvent for 12 h, and then rinsed with DMC to remove the lithium salts attached to the negative electrode. After drying, the protective layer of the main area of the negative electrode is analyzed by laser irradiation from top to bottom. The spectral analysis results show that 100% lithium is present, indicating that the protective layer contains elemental lithium. At least 5 different areas are tested and analyzed.
[0019] In this invention, whether the protective layer contains lithium carbonate can be determined by conventional testing methods in the art, such as by X-ray diffraction or Raman spectroscopy, and the presence of lithium carbonate can be determined by characteristic peaks.
[0020] In this invention, the surface of the negative electrode active layer facing away from the negative electrode current collector includes several grooves, and the negative electrode sheet includes a first edge. The included angle between the grooves and the first edge is θ, 10°≤θ≤70°, for example, 10°, 12°, 14°, 16°, 20°, 25°, 30°, 35°, 40°, 45°, 50°, 60°, or 70°. It should be noted that the grooves and the first edge intersect to form two complementary angles, and the included angle θ refers to the acute angle. In one specific example, the first edge of the negative electrode sheet extends, for example, along the width direction of the battery; in another specific example, the first edge of the negative electrode sheet extends, for example, along the length direction of the battery; in yet another specific example, the first edge of the negative electrode sheet extends obliquely along the width direction of the battery.
[0021] In this invention, at least a portion of the protective layer is located on the surface of the groove. "At least a portion" can be understood as meaning that the area of the protective layer projected onto the surface of the groove and onto the surface of the negative electrode can be less than 100% or equal to 100%.
[0022] In this invention, the groove can be prepared by conventional methods in the art, such as by laser processing.
[0023] The immense energy generated during the formation of the groove can disrupt the bonding network in the negative electrode active layer. By forming a protective layer within the groove, this layer absorbs the expansion stress of the silicon-carbon material particles located within the groove during battery cycling, preventing these particles from being squeezed together and detached. Simultaneously, the lithium carbonate within the protective layer maintains normal lithium ion insertion and extraction. The connection between the silicon-carbon material and lithium carbonate ensures a stable and unobstructed lithium ion transport pathway, improving lithium replenishment efficiency and active lithium compensation during cycling. Furthermore, adjusting the angle θ between the groove and the first edge of the negative electrode sheet prevents powder shedding from the negative electrode edge, improving the stability of the negative electrode active layer and maintaining the stability of the conductive and bonding networks. This ensures that the active lithium released during cycling can stably and efficiently perform its compensation function, improving the battery's initial coulombic efficiency. The angle θ also increases the electrolyte wetting space, increasing the electrolyte storage capacity of the negative electrode sheet and providing a continuous channel for lithium ion transport, preventing lithium plating due to insufficient electrolyte wetting.
[0024] In this invention, θ can be determined in a conventional manner in the art. Specifically, after discharging the battery to 0% SOC, the negative electrode is disassembled and removed. It is then soaked in DMC solvent for 12 hours and rinsed with DMC to remove the lithium salt attached to the electrode. The angle between the first edge and the groove is measured under a 3D microscope using an angle measuring tool. The average value of the five different angles is θ.
[0025] In this invention, the average thickness of the protective layer is 0.01 μm to 0.5 μm, for example, 0.01 μm, 0.02 μm, 0.04 μm, 0.06 μm, 0.08 μm, 0.1 μm, 0.15 μm, 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm or 0.5 μm.
[0026] like Figure 1 The diagram shown is a schematic diagram of the negative electrode sheet along the thickness direction in an embodiment of the present invention. The negative electrode sheet includes a negative current collector 10, a positive and negative active layer 11 located on the surface of the negative current collector 10, and a protective layer 12 located on the surface of the negative active layer 11. The protective layer 12 includes elemental lithium 12.
[0027] The protective layer is formed by surface passivation of a partially vapor-deposited lithium metal layer. When the thickness of the protective layer is too small (e.g., <0.01μm), it cannot protect the lithium elemental replenished to the silicon-carbon material. The lithium elemental still has the possibility of contact with the outside air, which increases the safety hazard and is not conducive to improving the furnace temperature safety performance of the battery. When the thickness of the protective layer is too large (e.g., >0.5μm), the proportion of the passivated lithium metal layer forming the protective layer is too high. If the thickness of the lithium metal layer is too small, it cannot adequately compensate for the active lithium consumed in the formation of the SEI film during the first charge, reducing the benefit of lithium replenishment. It is also difficult to retain lithium elemental for subsequent slow release replenishment in the negative electrode sheet, which is not conducive to further improvement of the battery's energy density and initial coulombic efficiency.
[0028] In this invention, the average thickness of the protective layer can be determined by conventional methods in the art, such as X-ray photoelectron spectroscopy (XPS), specifically as follows: the battery is discharged to 0% SOC, the negative electrode is disassembled and removed, soaked in dimethyl carbonate (DMC) solvent for 12 hours, and then rinsed with DMC to remove the lithium salt attached to the negative electrode. After drying, the protective layer of the main area of the negative electrode is analyzed by XPS with a sputtering depth of 10 nm. After each sputtering, a fine spectral scan of lithium is performed. The sputtering-scanning cycle is repeated until Li exists as elemental lithium. At this point, the total sputtering depth is the thickness of the protective layer. The thickness of at least 5 regions is measured and the average value is taken as the average thickness of the protective layer.
[0029] In this invention, the battery includes a negative electrode tab extending from one side edge of the negative electrode current collector. Along the extending direction of the negative electrode tab, the negative electrode sheet includes a first region and a second region, the first region being close to the negative electrode tab and the second region being away from the negative electrode tab.
[0030] In this invention, the mass ratio of element Li to element Si in the first region is a1, and the mass ratio of element Li to element Si in the second region is a2, where a1 < a2.
[0031] In one embodiment, a1 and a2 satisfy: 30%≤a1 / a2≤90%, for example, 30%, 32%, 34%, 36%, 38%, 40%, 45%, 50%, 55%, 60%, 70%, 80% or 90%.
[0032] In this invention, the first region and the second region include the lithium carbonate.
[0033] The inclusion of lithium carbonate in the first and second regions indicates that the elemental lithium portions located in these regions undergo passivation to form a protective layer. This layer protects the elemental lithium in the negative electrode active layer, preventing it from reacting chemically with external air and moisture, reducing safety hazards in lithium-ion batteries, and improving the lithium-ion replenishment effect. Consequently, it further improves the initial coulombic efficiency and cycle stability of high-energy-density batteries. Simultaneously, it increases the surface roughness of the negative electrode, improves the electrolyte contact angle, enhances the wettability of the electrolyte to the negative electrode, and improves lithium-ion transport efficiency.
[0034] In this invention, along the extending direction of the negative electrode tab, the negative electrode sheet has at least a first negative electrode region and a second negative electrode region, the first negative electrode region being close to the negative electrode tab, and the second negative electrode region being away from the negative electrode tab, wherein the thickness of the negative electrode active layer located in the first negative electrode region is less than the thickness of the negative electrode active layer located in the second negative electrode region.
[0035] In this invention, the orthographic projection of the first region and the orthographic projection of the first negative pole region at least partially overlap. Here, "at least partially overlap" can be understood as the orthographic projections of the first region and the second negative pole region potentially overlapping partially or completely. Preferably, the orthographic projection of the first region completely covers the orthographic projection of the first negative pole region.
[0036] The active layer of the first negative electrode region, located near the negative electrode tab, is thinner, resulting in a relatively low capacity. If a first region with low lithium-silicon content is not included, or if the overlap between the first region and the first negative electrode region's orthogonal projection is low, the local lithium concentration may exceed its capacity limit. During subsequent charging, excess lithium cannot be intercalated into the negative electrode and instead deposits as metallic lithium on the negative electrode surface, forming lithium dendrites. This is detrimental to further improving the battery's cycle stability and thermal safety. Therefore, setting a1 < a2 and 30% ≤ a1 / a2 ≤ 90% on the negative electrode side reduces the amount of active lithium compensation in the first region of the negative electrode sheet. The overlap between the first region and the first negative electrode region's orthogonal projection reduces the amount of lithium replenishment in the first region, thereby reducing the concentration of lithium ions intercalating into the first negative electrode region. This ensures that the first negative electrode region does not reach the lithium plating critical point due to excessive lithium replenishment, ensuring stable and orderly lithium ion extraction / intercalation in this region. This fundamentally eliminates lithium plating caused by capacity mismatch and further improves the battery's cycle stability.
[0037] When a1 / a2 is too small (e.g., <30%), the amount of lithium replenishment in the first region is too low. Although the lithium plating problem is avoided, the active lithium compensation is too low, resulting in insufficient lithium replenishment. The active lithium consumed in forming the SEI film during the first charge is not adequately compensated, which is not conducive to improving the battery's first coulombic efficiency and energy density. When a1 / a2 is too large (e.g., >90%), the amount of lithium replenishment in the first region is close to that in the second region. Excessive active lithium cannot be fully received by the first negative electrode region and accumulates and deposits on the negative electrode surface, thus aggravating lithium plating.
[0038] In this invention, a1 and a2 can be obtained by conventional testing methods in the art, such as by inductively coupled plasma atomic emission spectrometry (ICP). Specifically, after the battery is discharged to 0% SOC, the negative electrode is disassembled and removed. After soaking in DMC solvent for 12 hours, it is rinsed with DMC solvent to remove the lithium salt attached to the negative electrode. Along the height direction of the negative electrode, the negative electrode active layer is scraped at one end of the tab extension and near the lower end to obtain the negative electrode active layer in the first region and the negative electrode active layer in the second region. About 0.1g of the negative electrode active layer in the first region is added to 10mL of hydrochloric acid and digested on a hot plate at 350℃ for 10min. After cooling, the volume is adjusted to 100ml, and then diluted 10 times. A portion of the solution is analyzed by an ICP spectrometer to obtain the mass content of Li and Si elements in the first region and calculate a2. The above operation is repeated for the negative electrode active layer in the second region to obtain a2.
[0039] In this invention, along the extending direction of the negative electrode tab, the negative electrode sheet extends beyond the positive electrode sheet by a dimension L, and the dimension of the first region is L1, where L1 > L.
[0040] The edge of the negative electrode extends beyond the positive electrode along the tab direction. The part that extends beyond the tab does not have a corresponding positive electrode. When L1>L, it can be ensured that the first region covers the part of the negative electrode that extends beyond the positive electrode, thereby reducing the amount of active lithium compensation in this region and avoiding excessive lithium storage that is difficult to utilize effectively and will result in lithium plating.
[0041] In this invention, along the extending direction of the negative electrode tab, the size of the second region is L2, and L1 and L2 satisfy: 2%≤L1 / L2≤16%, for example, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or 16%.
[0042] In this invention, L1 is 2mm to 5mm, for example, 2mm, 2.2mm, 2.4mm, 2.6mm, 3mm, 3.5mm, 4mm, 4.5mm or 5mm.
[0043] In this invention, L2 is 30mm to 90mm, for example, 30mm, 32mm, 34mm, 36mm, 40mm, 45mm, 50mm, 55mm, 60mm, 70mm, 80mm or 90mm.
[0044] Adjusting the dimensions of the first and second regions and their relationship allows for the division of the first and second regions within a reasonable range, ensuring effective lithium replenishment while suppressing the risk of lithium plating. When L1 / L2 is too large (e.g., >16%), the first region is too large compared to the second region, compressing the effective area of the second region, which has more abundant active lithium and higher lithium replenishment efficiency. This leads to a decrease in the overall active lithium concentration of the negative electrode, which is detrimental to improving the battery's initial coulombic efficiency and energy density. When L1 / L2 is too small (e.g., <2%), the first region is too small compared to the second region, resulting in a decrease in the coverage of the second positive electrode region. It may even fail to completely cover the portion of the negative electrode extending beyond the positive electrode in the tab extension direction. This leads to excessive lithium replenishment at the edges, causing localized lithium plating during charging, which is detrimental to the battery's cycle stability and safety performance.
[0045] In this invention, along the extending direction of the negative electrode tab, the negative electrode sheet further includes a third region, the third region being opposite to the negative electrode tab, and the second region being located between the first region and the third region.
[0046] In this invention, the mass content ratio of element Li to element Si in the third region is a3, and a3 and a2 satisfy: 30%≤a3 / a2≤90%, for example, 30%, 32%, 34%, 36%, 38%, 40%, 45%, 50%, 55%, 60%, 70%, 80% or 90%.
[0047] In this invention, along the extension direction of the negative electrode tab, the size of the third region is L3, and L3 and L2 satisfy: 2%≤L3 / L2≤16%, for example, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or 16%.
[0048] In this invention, L3 is 2mm to 5mm, for example, 2mm, 2.2mm, 2.4mm, 2.6mm, 3mm, 3.5mm, 4mm, 4.5mm or 5mm.
[0049] It is understood that, along the extension direction of the negative electrode tab, the third region is located at the bottom edge of the negative electrode sheet, and the third region includes the portion of the negative electrode sheet that extends beyond the positive electrode sheet.
[0050] like Figure 2The diagram shown is a structural schematic of a negative electrode sheet along the extension direction of the tab in an embodiment of the present invention. The negative electrode sheet 1 includes a negative tab 14. Along the extension direction of the negative tab 14, the negative electrode sheet has a first region 31 close to the negative tab 14, a third region 33 away from the negative tab 14, and a second region 32 located between the first region 31 and the third region 33.
[0051] The third region, extending beyond the positive electrode from the bottom of the negative electrode sheet, is set to 30% ≤ a3 / a2 ≤ 90%. This reduces the amount of active lithium compensation in the third region of the negative electrode, improves the matching degree of lithium-ion carrying capacity between the positive and negative electrodes, and ensures stable and orderly lithium ion extraction / insertion in this region. This fundamentally eliminates lithium plating caused by capacity mismatch and further improves the cycle stability of the battery. When a3 / a2 is too small (e.g., <30%), the amount of lithium replenishment in the third region is too low. Although the lithium plating problem is avoided, the insufficient active lithium compensation leads to inadequate lithium replenishment. The active lithium consumed in forming the SEI film during the first charge is not adequately compensated, which is detrimental to the improvement of the battery's initial coulombic efficiency and energy density. When a3 / a2 is too large (e.g., >90%), the amount of lithium replenishment in the third region is close to that in the second region. At this time, the negative electrode stores excess lithium, and the excess active lithium accumulates and deposits on the negative electrode surface, thus aggravating lithium plating.
[0052] Adjusting the dimensions of the second and third regions and their relationship allows for the division of these regions within a reasonable range, ensuring effective lithium replenishment while suppressing the risk of lithium plating. When L3 / L2 is too large (e.g., >16%), the third region is too large compared to the second region, compressing the effective area of the second region, which has more abundant active lithium and higher lithium replenishment efficiency. This leads to a decrease in the overall active lithium concentration of the negative electrode, making it difficult to protect the elemental lithium replenished to the silicon-carbon material, which is detrimental to improving the battery's initial coulombic efficiency and energy density. Conversely, when L3 / L2 is too small (e.g., <2%), the third region is too small compared to the second region, resulting in reduced coverage of the second positive electrode region, or even failing to completely cover the portion of the negative electrode extending beyond the positive electrode. This leads to excessive lithium replenishment at the edges, causing localized lithium plating during charging, which is detrimental to the battery's cycle stability and safety performance.
[0053] In this invention, L1, L2, L3 and L can be obtained by conventional testing methods in the art, specifically as follows: after the battery is discharged to 0% SOC, the negative electrode is disassembled, dried and measured by a 3D microscope.
[0054] In this invention, a3 can be determined by referring to the test methods of a1 and a2.
[0055] In this invention, along the extending direction of the negative electrode tab, the negative electrode tab includes a fourth region and a fifth region, the fourth region being located between the fifth region and the electrode assembly.
[0056] like Figure 3 The diagram shown is a schematic diagram of the structure of the negative electrode tab in one embodiment of the present invention. The negative electrode tab 14 has a fourth region 34 and a fifth region 35, with the fourth region 34 located between the fifth region 35 and the electrode assembly.
[0057] In this invention, the surface of the fourth region comprises elemental lithium and a protective layer located on the outer surface of the fourth region, the protective layer comprising the lithium carbonate. The presence of elemental lithium or lithium carbonate in the fourth region can be determined using conventional testing methods in the art, such as X-ray diffraction or Raman spectroscopy.
[0058] A small amount of metallic lithium is deposited at the negative electrode tab in the fourth region. A protective layer is needed to protect the highly active metallic lithium from chemical reactions with air and moisture, which could lead to safety risks. In addition, the elemental lithium under the protective layer cannot react with the copper foil and can be retained until charge and discharge, where it is slowly released to compensate for the loss of active lithium during battery cycling, further improving the battery's cycle stability and initial coulombic efficiency.
[0059] In this invention, the term 0% SOC refers to discharging the battery at 0.1C to the lower limit voltage (e.g., 2.8V).
[0060] It should be noted that in this invention, the numerical representations such as "first" and "second" are only used to distinguish different substances or methods of use, and do not represent a difference in order.
[0061] The present invention will be described in detail below through embodiments. The embodiments described herein are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0062] In the following examples, unless otherwise specified, all materials used are commercially available analytical grade.
[0063] The following examples illustrate the battery of the present invention.
[0064] Example 1: (1) Preparation of the positive electrode: Lithium cobalt oxide, conductive carbon black, carbon nanotubes, and polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 97.6:0.9:0.45:1.05 and then placed in N-methylpyrrolidone (NMP) and stirred until homogeneous to obtain a positive electrode active slurry. The positive electrode active slurry was then uniformly coated on both sides of an aluminum foil to obtain a positive electrode active layer. The positive electrode sheet was then obtained by drying, rolling, and die-cutting.
[0065] (2) Preparation of the negative electrode: Silicon carbon material, artificial graphite, conductive carbon black, sodium carboxymethyl cellulose (CMC-Na), and styrene-butadiene rubber (SBR) were mixed in a ratio of 20:77.2:0.05:1.35:1.4 and placed in deionized water. After stirring evenly, a negative electrode active slurry was prepared. This negative electrode active slurry was uniformly coated on both sides of a carbon-coated copper foil to obtain a negative electrode active layer. After drying, rolling, and die-cutting, and then cleaning and sheet forming, a negative electrode sheet was obtained. The area near the negative electrode tab forms the first negative electrode region, where the thickness of the negative electrode active layer is reduced. An inclined groove with an angle of θ = 55° is prepared on the side of the negative electrode active layer away from the negative electrode current collector by laser processing. Shielding baffles are set at the top and bottom of the negative electrode sheet to divide the negative electrode sheet into a first region (L1 = 3.6 mm), a second region (L2 = 45 mm), and a third region (L3 = 3.9 mm). A certain amount of metallic lithium is deposited in each region of the negative electrode sheet by physical vapor deposition at a deposition temperature of 500℃. Subsequently, the negative electrode sheet with the metallic lithium layer is placed in a mixed gas of 20% CO2 and 80% Ar and passivated at 70℃ for 30 min to form a protective layer with an average thickness of 0.34 μm. At the same time, a fourth region with elemental lithium and a protective layer and a fifth region without elemental lithium and a protective layer are formed on the negative electrode tab.
[0066] At this time, a1 / a2 is 67%, a3 / a2 is 58%, L1 / L2 is 8%, and L3 / L2 is 8.7%. The orthogonal projection of the first region completely covers the first negative pole region.
[0067] (3) Diaphragm: The membrane comprises a polyethylene layer and a boehmite layer coated on one side of the polyethylene layer, and a polyvinylidene fluoride layer coated on the outside of the polyethylene layer and the boehmite layer. The membrane thickness is 8 μm.
[0068] (4) Preparation of electrolyte: Ethylene carbonate (EC), diethyl carbonate (DEC), and dimethyl carbonate (EMC) were mixed in a mass ratio of 1:1:1 to obtain a base solvent. Based on the total weight of the electrolyte, 3% of 1,3-propanesulfonyl lactone (PS), 12% of fluoroethylene carbonate (FEC), 2% of 1,3,6-hexanetrionitrile (HTCN), and 1M of LiPF6 were added to the solvent and mixed thoroughly to obtain the electrolyte.
[0069] (5) Battery fabrication: The pre-cut positive electrode sheet, separator, and negative electrode sheet are stacked to form a core. After the tabs are welded, the core is placed in a prepared aluminum-plastic film, then injected with liquid and sealed to complete the preparation. It is then left to stand for 48 hours for aging, followed by formation activation, and finally capacity testing to obtain the battery. The negative electrode sheet extends beyond the positive electrode sheet along the extension direction of the negative electrode tab, with its dimension L < L1.
[0070] (6) Preparation of the negative electrode half-cell: Take the negative electrode sheet prepared in (1), use a lithium metal sheet as the counter electrode and a 1 mol / L lithium hexafluorophosphate-ethylene carbonate / dimethyl carbonate (volume ratio of 1:1) solution as the electrolyte to form a negative electrode half cell.
[0071] Example 2: (1) Preparation of the positive electrode: Lithium cobalt oxide, conductive carbon black, carbon nanotubes and PVDF were mixed in a mass ratio of 97.6:0.9:0.45:1.05 and placed in NMP. The mixture was stirred evenly to obtain a positive electrode active slurry. The positive electrode active slurry was uniformly coated on both sides of an aluminum foil to obtain a positive electrode active layer. The positive electrode sheet was then obtained by drying, rolling and die-cutting.
[0072] (2) Preparation of the negative electrode: Silicon-carbon material, artificial graphite, conductive carbon black, CMC-Na, and SBR were mixed in a ratio of 20:77.2:0.05:1.35:1.4 and placed in deionized water. After stirring evenly, a negative electrode active slurry was prepared. This negative electrode active slurry was uniformly coated on both sides of a carbon-coated copper foil to obtain a negative electrode active layer. After drying, rolling, and die-cutting, and then cleaning and sheet forming, a negative electrode sheet was obtained. The area near the negative electrode tab forms the first negative electrode region, where the thickness of the negative electrode active layer is reduced. An inclined groove with an angle of θ = 12° is prepared on the side of the negative electrode active layer away from the negative electrode current collector by laser processing. Shielding baffles are set at the top and bottom of the negative electrode sheet to divide the negative electrode sheet into a first region (L1 = 2.3 mm), a second region (L2 = 87 mm), and a third region (L3 = 3.9 mm). A certain amount of metallic lithium is deposited in each region of the negative electrode sheet by physical vapor deposition at a deposition temperature of 500℃. Subsequently, the negative electrode sheet with the metallic lithium layer is placed in a mixed gas of 5% CO2 and 95% Ar at 70℃ for passivation for 30 min to form a protective layer with an average thickness of 0.02 μm. At the same time, a fourth region with elemental lithium and a protective layer and a fifth region without elemental lithium and a protective layer are formed on the negative electrode tab.
[0073] At this time, a1 / a2 is 30%, a3 / a2 is 33%, L1 / L2 is 2.6%, L3 / L2 is 2.3%, and the orthogonal projection of the first region completely covers the first negative pole region.
[0074] (3) Diaphragm: The membrane comprises a polyethylene layer and a boehmite layer coated on one side of the polyethylene layer, and a polyvinylidene fluoride layer coated on the outside of the polyethylene layer and the boehmite layer. The membrane thickness is 8 μm.
[0075] (4) Preparation of electrolyte: EC, DEC, and EMC were mixed in a mass ratio of 1:1:1 to obtain the base solvent. Based on the total weight of the electrolyte, 3% PS, 12% FEC, 2% HTCN, and 1M LiPF6 were added to the solvent and mixed evenly to obtain the electrolyte.
[0076] (5) Battery fabrication: The pre-cut positive electrode sheet, separator, and negative electrode sheet are stacked to form a core. After the tabs are welded, the core is placed in a prepared aluminum-plastic film, then injected with liquid and sealed to complete the preparation. It is then left to stand for 48 hours for aging, followed by formation activation, and finally capacity testing to obtain the battery. The negative electrode sheet extends beyond the positive electrode sheet along the extension direction of the negative electrode tab, with its dimension L < L1.
[0077] (6) Preparation of the negative electrode half-cell: Take the negative electrode sheet prepared in (1), use a lithium metal sheet as the counter electrode and a 1 mol / L lithium hexafluorophosphate-ethylene carbonate / dimethyl carbonate (volume ratio of 1:1) solution as the electrolyte to form a negative electrode half cell.
[0078] Example 3: (1) Preparation of the positive electrode: Lithium cobalt oxide, conductive carbon black, carbon nanotubes and PVDF were mixed in a mass ratio of 97.6:0.9:0.45:1.05 and placed in NMP. The mixture was stirred evenly to obtain a positive electrode active slurry. The positive electrode active slurry was uniformly coated on both sides of an aluminum foil to obtain a positive electrode active layer. The positive electrode sheet was then obtained by drying, rolling and die-cutting.
[0079] (2) Preparation of the negative electrode: Silicon-carbon material, artificial graphite, conductive carbon black, CMC-Na, and SBR were mixed in a ratio of 20:77.2:0.05:1.35:1.4 and placed in deionized water. After stirring evenly, a negative electrode active slurry was prepared. This negative electrode active slurry was uniformly coated on both sides of a carbon-coated copper foil to obtain a negative electrode active layer. After drying, rolling, and die-cutting, and then cleaning and sheet forming, a negative electrode sheet was obtained. The area near the negative electrode tab forms the first negative electrode region, where the thickness of the negative electrode active layer is reduced. An inclined groove with an angle of θ = 67° is prepared on the side of the negative electrode active layer away from the negative electrode current collector by laser processing. Shielding baffles are set at the top and bottom of the negative electrode sheet to divide the negative electrode sheet into a first region (L1 = 4.7 mm), a second region (L2 = 30 mm), and a third region (L3 = 4.8 mm). A certain amount of metallic lithium is deposited in each region of the negative electrode sheet by physical vapor deposition at a deposition temperature of 500℃. Subsequently, the negative electrode sheet with the metallic lithium layer is placed in a mixed gas of 25% CO2 and 75% Ar and passivated at 70℃ for 30 min to form a protective layer with an average thickness of 0.48 μm. At the same time, a fourth region with elemental lithium and a protective layer and a fifth region without elemental lithium and a protective layer are formed on the negative electrode tab.
[0080] At this point, a1 / a2 is 88%, a3 / a2 is 33%, L1 / L2 is 15.7%, and L3 / L2 is 16%. The orthogonal projection of the first region completely covers the first negative pole region.
[0081] (3) Diaphragm: The membrane comprises a polyethylene layer and a boehmite layer coated on one side of the polyethylene layer, and a polyvinylidene fluoride layer coated on the outside of the polyethylene layer and the boehmite layer. The membrane thickness is 8 μm.
[0082] (4) Preparation of electrolyte: EC, DEC, and EMC were mixed in a mass ratio of 1:1:1 to obtain the base solvent. Based on the total weight of the electrolyte, 3% PS, 12% FEC, 2% HTCN, and 1M LiPF6 were added to the solvent and mixed evenly to obtain the electrolyte.
[0083] (5) Battery fabrication: The pre-cut positive electrode sheet, separator, and negative electrode sheet are stacked to form a core. After the tabs are welded, the core is placed in a prepared aluminum-plastic film, then injected with liquid and sealed to complete the preparation. It is then left to stand for 48 hours for aging, followed by formation activation, and finally capacity testing to obtain the battery. The negative electrode sheet extends beyond the positive electrode sheet along the extension direction of the negative electrode tab, with its dimension L < L1.
[0084] (6) Preparation of the negative electrode half-cell: Take the negative electrode sheet prepared in (1), use a lithium metal sheet as the counter electrode and a 1 mol / L lithium hexafluorophosphate-ethylene carbonate / dimethyl carbonate (volume ratio of 1:1) solution as the electrolyte to form a negative electrode half cell.
[0085] Example 4 group: This set of examples is used to verify the impact of changes in the "groove setting", as detailed below: Example 4a is based on Example 1, except that θ is 0°; Example 4b is based on Example 1, except that no groove is provided.
[0086] Example 5: Based on Example 1, the only difference is that the mixed gas composition is 30% CO2 and 70% Ar, and the average thickness of the protective layer is 0.6 μm.
[0087] Example 6 group: This set of examples is used to verify the impact of changes in "a1 / a2, L1 / L2", which is achieved by adjusting the position of the baffle, as follows: Example 6a is based on Example 3, except that L1 is 20 mm and a1 / a2 is 23%; Example 6a is based on Example 2, except that L1 is 1.2 mm and a1 / a2 is 95%.
[0088] Example 7: Based on Embodiment 1, the difference is that the orthogonal projection portion of the first region covers the first negative electrode region.
[0089] Example 8 group: This set of examples is used to verify the impact of changes in "a3 / a2, L3 / L2", which is achieved by adjusting the position of the baffle, as follows: Example 8a is based on Example 3, except that L1 is 9 mm and a3 / a2 is 25%; Example 8b is based on Example 2, except that L1 is 1.3 mm and a3 / a2 is 97%.
[0090] Example 9: Based on Example 1, the difference is that the fourth region has no protective layer.
[0091] Example 9 group: This set of embodiments is used to verify the impact of changes in the "settings of the first region and the third region", as detailed below: Example 9a is based on Example 1, except that a first region is not provided; Example 9b is based on Example 1, except that a second region is not provided.
[0092] Comparative Example 1: Based on Example 1, the difference is that no metallic lithium is deposited on the surface of the negative electrode active layer, nor is a passivation protective layer applied.
[0093] Comparative Example 2: Based on Example 1, the difference is that the surface of the negative electrode active layer is not passivated with a protective layer.
[0094] Test example: (1) First Coulomb efficiency: The negative electrode half-cells prepared in the embodiments and comparative examples of this invention were allowed to stand at 25℃±5℃ for 10 min; then charged at a constant current of 0.1C to the upper limit cutoff voltage of 4.55V (cutoff current 0.02C), and the battery charging capacity was recorded; after standing for 10 min, they were discharged at a constant current of 0.1C to the lower limit voltage of 2.8V, and the battery discharging capacity was recorded. The initial coulombic efficiency = (discharge capacity / charge capacity) × 100%. The test results are recorded in Table 1.
[0095] (2) 130℃ furnace temperature test: The batteries prepared in the embodiments and comparative examples of this invention were discharged to 2.8V at a discharge rate of 0.2C at room temperature, and then charged to the upper limit voltage of 4.55V at a discharge rate of 0.5C, with a cutoff current of 0.02C. The fully charged batteries were then placed in an oven and heated at a rate of 5±2℃. Once the oven temperature reached 130±2℃, it was kept constant for 60 minutes. A battery that did not catch fire or explode was considered to have passed the test. Fifteen batteries were tested in each group, and the pass rate was recorded as N / 15, meaning N out of 15 batteries passed the test. The test results are recorded in Table 1.
[0096] (3) Energy density test: The batteries prepared in the embodiments and comparative examples of this invention were tested using a Xinwei battery tester. They were charged at 0.5C to the upper limit voltage of 4.55V (cutoff at 0.05C) and discharged at 0.5C to the lower limit voltage of 2.8V, repeated three times. The discharge energy of the third discharge was taken as the battery energy Q. The width and height of the battery were measured using a 2.5D microscope, and the fully charged thickness was measured using a PPG thickness meter. The energy density is then calculated as Q / (width × height × thickness), and the results are recorded in Table 1.
[0097] (4) Lithium plating test: The batteries prepared in the embodiments and comparative examples of this invention were subjected to the following conditions at 25℃±2℃: first, discharge at 0.2C to the lower limit voltage of 2.8V, let stand for 10 minutes, then charge at 0.7C to the upper limit voltage of 4.55V, and let stand for 10 minutes. Subsequently, they were charged at a constant current and constant voltage of 3.5C to full charge (cut off at 0.02C), then discharged at 0.7C. This charge-discharge cycle was repeated for 50T. The batteries were then disassembled to observe the lithium plating state on the surface of the negative electrode. The criteria for judging the lithium plating phenomenon on the negative electrode were as follows: "0" for no lithium plating; "1" for the lithium plating area being less than 3% of the total negative electrode area; "2" for the lithium plating area being 3%-5% of the total negative electrode area; "3" for the lithium plating area being greater than 5% and less than or equal to 10% of the total negative electrode area; and "4" for the lithium plating area being greater than 15% of the total negative electrode area. The test results are recorded in Table 1.
[0098] Table 1: As can be seen from Table 1, the lithium-ion battery prepared by this invention, compared with the comparative example, takes into account the first coulombic efficiency, energy density and furnace temperature safety performance.
[0099] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A battery, characterized in that, The battery includes an electrode assembly, which includes a positive electrode sheet, a separator, and a negative electrode sheet stacked together. The negative electrode sheet includes a negative electrode current collector and a negative electrode active layer located on at least one side surface of the negative electrode current collector. The negative electrode active layer includes a negative electrode active material, which includes a silicon-carbon material. A protective layer is provided on the side of the negative electrode active layer opposite to the negative electrode current collector. The protective layer includes lithium carbonate, and the silicon-carbon material and at least a portion of the lithium carbonate are connected. The protective layer also includes elemental lithium.
2. The battery according to claim 1, wherein, The surface of the negative electrode active layer facing away from the negative electrode current collector includes several grooves, and the negative electrode sheet includes a first edge. The angle between the grooves and the first edge is θ, where 10°≤θ≤70°. At least a portion of the protective layer is located on the surface of the groove.
3. The battery according to claim 1 or 2, wherein, The average thickness of the protective layer is 0.01 μm to 0.5 μm.
4. The battery according to claim 1 or 2, wherein, The battery includes a negative electrode tab extending from one edge of the negative electrode current collector. Along the extending direction of the negative electrode tab, the negative electrode sheet includes a first region and a second region. The first region is close to the negative electrode tab, and the second region is away from the negative electrode tab. The mass ratio of element Li to element Si in the first region is a1, and the mass ratio of element Li to element Si in the second region is a2, where a1 < a2. Preferably, a1 and a2 satisfy: 30%≤a1 / a2≤90%.
5. The battery according to claim 4, wherein, Both the first region and the second region include the lithium carbonate.
6. The battery according to claim 4, wherein, Along the extending direction of the negative electrode tab, the negative electrode sheet has at least a first negative electrode region and a second negative electrode region. The first negative electrode region is close to the negative electrode tab, and the second negative electrode region is away from the negative electrode tab. The thickness of the negative electrode active layer located in the first negative electrode region is less than the thickness of the negative electrode active layer located in the second negative electrode region. Preferably, the orthographic projection of the first region and the orthographic projection of the first negative pole region at least partially overlap.
7. The battery according to claim 4, wherein, Along the extending direction of the negative electrode tab, the negative electrode sheet extends beyond the positive electrode sheet by a dimension L, and the dimension of the first region is L1, where L1 > L; And / or, along the extension direction of the negative electrode tab, the size of the second region is L2, where L1 and L2 satisfy: 2% ≤ L1 / L2 ≤ 16%; Preferably, L1 is 2mm~5mm; Preferably, L2 is 30mm~90mm.
8. The battery according to claim 4, wherein, Along the extending direction of the negative electrode tab, the negative electrode sheet further includes a third region, the third region being opposite to the negative electrode tab, and the second region being located between the first region and the third region; And / or, the mass content ratio of element Li to element Si in the third region is a3, and a3 and a2 satisfy: 30%≤a3 / a2≤90%.
9. The battery according to claim 8, wherein, Along the extension direction of the negative electrode tab, the size of the third region is L3, and L3 and L2 satisfy: 2%≤L3 / L2≤16%; Preferably, L3 is 2mm to 5mm.
10. The battery according to claim 4, wherein, Along the extending direction of the negative electrode tab, the negative electrode tab includes a fourth region and a fifth region, the fourth region being located between the fifth region and the electrode assembly; Preferably, the surface of the fourth region includes elemental lithium and a protective layer located on the outer surface of the fourth region, the protective layer including the lithium carbonate.